Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura) - Komai, Tomoyuki; Shimetsugu, Miho; Ng, Peter K.l. (Zootaxa, 2019)
A poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, originally described on the basis of an immature male holotype and an immature female paratype from Singapore, is rediscovered and rediagnosed on the basis of material from Thailand, the Philippines and the Ryukyu Islands (Japan). In addition, a new species closely related to P. punctulata, P. parilis, is described and illustrated on the basis of material from Mie Prefecture, Honshu mainland of Japan. The new species is distinguished from P. punctulata by the coarser granules bordering the lateral carapace margins and the different shape of the gonopods. Pseudophilyra tridentata Miers, 1879, is also compared with P. punctulata and P. parilis n. sp. because of the close similarities in the overall morphology of the carapace and appendages, but can easily be differentiated by the smoother carapace and thoracic sternum surface, different shape of the carapace and the stouter cheliped palm. It is possible that previous records of P. tridentata outside Japan might contain more than one species.